Implementasi Saintifik Terintegrasi Make a Match dengan Reward Edugames dalam Pembelajaraan - Purnama, Herwulan Irine (Jurnal Didaktika Pendidikan Dasar, 2023)
This research aims to learn about the learning activities of learners in the Scientific Learning Process which is integrated with the “Make a Match” Strategy and “Reward Education Games” and also to learn about how to apply in the Scientific Learning Process which is integrated with “Make a Match” Strategy and “Reward Education Games’. This study was conducted in class VI SDN 37 Southeast Pontianak with a total of 26 students which consisted of 16 male students and 10 female students in the subject of social studies. The results of the research obtained are learning by innovating the development of a scientific approach that is integrated with “Make a Match” and “Reward Education Games” that are done well to increase the student's learning activities of class VI at SDN 37 Southeast Pontianak. The absorption of students to learning showed there are some students who get scores above the KKM reaching 84.6%.